Use of the electromechanical impedance method in the detection of inclusions: application to mammary tumors. (May 2021) - Menegaz, Gabriela Lima; Tsuruta, Karina Mayumi; Finzi Neto, Roberto Mendes; Steffen, Valder; Araujo, Cleudmar Amaral; Guimarães, Gilmar
Breast cancer is a public health problem and has the highest incidence and mortality in the female population worldwide. Early detection of breast cancer is essential for reducing the morbidity and mortality associated with this disease. Some methods for detecting breast tumors include ultrasonography, magnetic resonance imaging, positron emission tomography, tomosynthesis, and mammography, which are recommended as screening techniques. Each method has its advantages and disadvantages, such as discomfort to the patient during examination, possible reactions to the contrast agent, radiation emission, operator dependence for the analysis of results, difficulty of detection in dense tissues, lack of access for people with disabilities or low mobility, high cost, and radioactive waste production. The main objective of this work is to apply the electromechanical impedance method to the detection of inclusions so that it can be used as an alternative to existing techniques for the detection of breast tumors. The application of the electromechanical impedance method using piezoelectric transducers, acting simultaneously as sensors and actuators, coupled to the analyzed structure allows the monitoring of mass, rigidity, and/or damping variations, and consequent detection of inclusions. The detection of inclusions is possible owing to damage metrics, which are statistical parameters capable of numerically representing the difference between two measurements before and after damage. In this work, silicone samples and phantom breast models were analyzed. In addition, it was observed that external heating imposed on the models and the presence of heat generation in the inclusions aided detection. This work presents important contributions in the analysis of structural behavior, expanding the applications of damage detection techniques to hyperplastic materials.